2006
DOI: 10.1159/000090463
|View full text |Cite
|
Sign up to set email alerts
|

Case Report of Optic Atrophy in Pansynostosis: An Unusual Presentation of Scalp Edema from Hair Braiding

Abstract: Pansynostosis (fusion of all cranial sutures) and optic atrophy were found as incidental CT scan and ophthalmological findings in an 8-year-old who presented to the emergency room with scalp edema from tight ‘cornrow’ hair braiding. Cranial vault expansion was successfully performed. Ophthalmological problems have stabilized but have not reversed. Late presentation of craniosynostosis and the pathophysiology of secondary optic atrophy are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 57 publications
1
7
0
Order By: Relevance
“…In 1984, we reported an infant with sagittal craniosynostosis probably due to suture fixation by a calcified subperiostal hematoma [4] . In this patient, histological findings of normal suture tissue beyond the limits of the hematoma tended to support our view, although it might also be that the calcified hematoma brought our attention to a preexisting condition, as the authors comment on the role of the scalp edema in their patient [1] .…”
supporting
confidence: 59%
See 2 more Smart Citations
“…In 1984, we reported an infant with sagittal craniosynostosis probably due to suture fixation by a calcified subperiostal hematoma [4] . In this patient, histological findings of normal suture tissue beyond the limits of the hematoma tended to support our view, although it might also be that the calcified hematoma brought our attention to a preexisting condition, as the authors comment on the role of the scalp edema in their patient [1] .…”
supporting
confidence: 59%
“…I read with great interest the paper by O'Hara et al [1] . I would like to refer to previous work from our hospital that might be of interest to the journal's readers.…”
Section: To the Editormentioning
confidence: 98%
See 1 more Smart Citation
“…Pansynostosis is a rare form of craniosynostosis that involves premature fusion of the cranial sutures (coronal, sagittal, metopic, and occipital) and, particularly in cases of late presentation, there are heightened clinical concerns, both functional and aesthetic. In untreated cases of pansynostosis and increased intracranial pressure (ICP), damage to the optic nerve progresses to optic atrophy and then blindness [2] .…”
Section: Introductionmentioning
confidence: 99%
“…In the patients with a mean age of 3.1 years (range 1-6 years), the optic atrophy was irreversible. He suggested that when there is increased ICP from craniosynostosis, patients have a poor prognosis [2] .…”
mentioning
confidence: 99%